Developmental assessments during the first 5 years of life in infants fed breast milk, cow's milk formula, or soy formula. Issue 7 (13th May 2020) - Bellando, Jayne; McCorkle, Ginger; Spray, Beverly; Sims, Clark R.; Badger, Thomas M.; Casey, Patrick H; Scott, Holly; Beall, Sarah R.; Sorensen, Seth T.; Andres, Aline
Abstract: Objective: To investigate the effects of infant feeding mode on childhood cognition and language as the differential effects of infant feeding on development remain understudied. Methods: Breastfed [BF, 174], cow's milk‐based formula‐fed [MF, 169], or soy protein‐based formula‐fed [SF, 161] children were longitudinally tested from age 3 to 60 months for neurodevelopment. Data were analyzed using mixed models while adjusting for multiple covariates. Sex differences were also assessed. Results: Standard scores were within established norms for all groups. There were no differences in mental development to age 24 months, yet BF children had significantly higher motor development scores at age 3 months than SF children (99.1 versus. 97.2). BF children had significantly higher composite intelligence scores at 48 months than MF and SF children (113.4 versus. 109.6 and 108.4, respectively) and higher verbal intelligence scores than SF children at 48 (105.6 versus. 100.7) and 60 months (109.8 versus. 105.9). Greater total language scores at ages 36 and 48 months were found in BF children compared with children fed MF or SF ( p < .001), with differences between sexes for auditory comprehension. Higher total language scores at age 60 months were found between BF and SF (105.0 versus. 100.1). Conclusion: Breastfeeding was associated with small, statistically significant, differences between children ages 3 and 5 years in verbal intelligence, expressive communication, and auditory comprehension with the latter having potential sexual dimorphic effects. Yet, these differences remain small and may not be of clinical relevance. Overall, MF and SF did not significantly differ. Abstract : Although breast milk is recommended as the ideal source of nutrition for the first year of life, there is little consensus in the literature regarding long‐term benefits of breastfeeding over cow's milk‐based or soy protein‐based formula feeding to children's neurodevelopment. We found that while a statistically significant advantage for breastfed children on language and cognitive tests exists, this is small in magnitude and not necessarily clinically relevant. All diets investigated provide adequate nutrients to sustain development up to age 60 months.